Abbreviated Care‐Process Quality Indicator Sets Linked with Survival and Functional Status Benefit in Older Adults Under Ambulatory Care. Issue 8 (15th July 2014) - Min, Lillian; Reuben, David; Karlamangla, Arun; Naeim, Arash; Prenovost, Katherine; Lee, Pearl; Wenger, Neil
<x xml:space="preserve">Abstract</x> Objectives To identify subsets of ambulatory care (outpatient only) quality indicators (QIs) associated with better survival and physical function outcomes. Design Observational cohort study. Setting Pooled data from the Assessing Care of Vulnerable Elders (ACOVE)‐1 study, which measured quality of care using 140 care‐process QIs, and the subsequent ACOVE‐2 study, which reduced the QIs to 69 ambulatory care QIs. Participants Older adults receiving ambulatory care (N = 1, 015). Measurements To prioritize and reduce the QIs into subsets, an expert panel rated each of 69 ambulatory care QIs for the strength of the link between process and benefit, defined as direct trial evidence on older adults or high expectation of benefit if a trial were conducted in older adults. This resulted in three reduced QI sets, reflecting their intended benefit: 17 QIs for survival (ACOVE Quality for Survival (AQS)‐17), five QIs to preserve function (AQF‐5), and 16 QIs to improve quality‐of‐life related to physical health and symptoms (AQQ‐16). Whether AQS‐17 would predict 3‐year survival was first tested in 1, 015 pooled ACOVE‐1 and ACOVE‐2 participants. Second, whether AQF‐5 (n = 74) and AQQ‐16 (n = 359) would predict change in the Physical Component Summary (PCS) score of the Medical Outcomes Study 12‐item Short‐Form Survey at 1 year was tested in the ACOVE‐2 cohort. Control variables were age, function‐based vulnerability, and comorbidity. Results Each 20‐percentage‐point increment in AQS‐17 was associated with survival (hazard ratio (HR) = 0.83, P = .01) up to 500 days but not thereafter. AQF‐5, but not AQQ‐16, predicted 1‐year improvement in PCS score (1.13‐points per 20%‐point increment in AQF‐5, P = .02). Conclusion Subsets of care processes can be linked with outcomes important to older adults. The AQS‐17 and AQF‐5 are potential tools for improving ambulatory care of older adults.